2005
DOI: 10.1203/01.pdr.0000155761.70710.c4
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Patterns of EphrinB2 and EphB2 in Human Umbilical Vessels and Congenital Venous Malformations

Abstract: Vascular malformations cause discomfort and pain in children and are often associated with skeletal hypertrophy. Their molecular basis is poorly understood. Ephrin ligands and Eph receptor tyrosine kinases are involved in embryonic vascular development. In mice, some ephrin/Eph family members show a complementary expression pattern in blood vessels, with ephrinB2 being expressed on arterial and EphB4 on venous endothelium. Targeted deletions of the genes reveal their essential roles for conduit vessel developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
5
27
0
2
Order By: Relevance
“…Yet, much less is known about their roles in the adult vasculature. The arteriovenous asymmetrical expression patterns of ephrin-B2 and EphB4 are maintained in the adult (Diehl et al, 2005;Korff et al, 2006). Likewise, ephrin-B2 expression is prominently upregulated during adult neovascularization (Gale et al, 2001;Hayashi et al, 2005;Shin et al, 2001) and arteriogenic vessel remodeling (Korff et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, much less is known about their roles in the adult vasculature. The arteriovenous asymmetrical expression patterns of ephrin-B2 and EphB4 are maintained in the adult (Diehl et al, 2005;Korff et al, 2006). Likewise, ephrin-B2 expression is prominently upregulated during adult neovascularization (Gale et al, 2001;Hayashi et al, 2005;Shin et al, 2001) and arteriogenic vessel remodeling (Korff et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9 After birth, EphB receptors and ephrin B ligands continue to be expressed by endothelial cells from various tissues; EphB2 and ephrin B2 display some selectivity for the arterial endothelium, whereas EphB4 is expressed in arterial and venous endothelium. 10 Functional assays in vitro have provided evidence that several EphB receptors and ephrin B ligands are active in human endothelial cells. Soluble dimeric forms of ephrin B ligands and EphB receptors, including Ephrin B1-Fc, ephrin B2-Fc, EphB4-Fc, and EphB1-Fc, promoted the growth, sprouting, migration, or assembly of capillary-like structures by various human endothelial cells, 6,[11][12][13][14][15][16] presumably by activating forward or reverse signaling.…”
Section: Introductionmentioning
confidence: 99%
“…29 But another study by Diehl et al 28 reported that in low-flow venous malformations also arterialization can occur, probably due to turbulent blood flow rather than arterial shear stress or tangential stress. Our findings indicate that similar mechanisms could contribute to the morphological alterations in varicose veins as well.…”
Section: Resultsmentioning
confidence: 99%
“…EphrinB2 is, however, expressed solely in arterial endothelial cells even in adult human vessels. 28 We had reported earlier that ephrinB4 is downregulated in varicose veins. 6 Taking this cue, we assessed the expression pattern of ephrinB2 in our study specimens to look for any dysregulation in the ephrinB4/ephrinB2 axis in varicose veins.…”
Section: The Arterial Specific Marker Ephrinb2 Is Upregulated In Varimentioning
confidence: 89%